3D-network polymer supported bimetallic γ-Fe2O3/Cu nanoparticles: As a new magnetic nanocomposite for the synthesis of new series functionalized benzodiazepines - Setareh Moradi; Roya Mozafari; Mohammad Ghadermazi (Applied Surface Science Advances)
In this work, a novel procedure for the synthesis of magnetic porous polymer of γ-Fe2O3 by the immobilization of copper (CuSO44H2O) coated with pyridine-2,6-di carbonyl-bis(thiourea) as a cross-linker was accomplished in order to fabricate three dimensional. The heterogeneous nanocatalystγ-Fe2O3-Cu@Calix/pyridine-2,6-dicarbonyl-bis(thiourea)was characterized by Transmission electron microscopies (TEM), Field emission scanning electron microscopy (SEM), Energy-dispersive X-ray spectrometer (EDS), Fourier transform infrared spectroscopy (FT-IR), Powder X-raydiffraction (XRD), Vibrating-sample magnetometer (VSM), Thermal gravimetric analysis (TGA), Atomic Force Microscopy (AFM),Inductively coupled Plasma (ICP) and Nitrogen adsorption desorption isotherm (BET)techniques and was used for the synthesis of 2,4 disubstituted-1, 5-benzodiazepine through the reaction of various substituted α-epoxyketones with o-phenylenediamine under green conditions. Advantages of this protocol include the clean reaction conditions, short reaction times, simple work-up, catalyst recyclability, environmental friendliness, suppression of side products, and stability during the reaction process.